Structural design optimization of a wind turbine blade using the genetic algorithm. Issue 12 (2nd December 2022) - Lee, Sang-Lae; Shin, Sang Joon
Abstract : With the increasing size of wind turbines in terms of their dimensions and capacity, structural design optimization for their blades is becoming all the more important. This study suggests an improved optimization framework. Blade optimization is performed in two stages: the ply lay-up pattern of the spar cap in the initial blade configuration based on the existing configuration, followed by the cross-sectional design optimization at several spanwise locations. The genetic algorithm is adopted and, in terms of the structural integrity evaluation, the final configuration results are found to be safe; in addition, the number of plies in the spar cap rapidly decreases through the two-stage design optimization procedure. As a result, the blade is lighter, and the lighter blade also reduces the applied load on the wind turbine. This will have an excellent effect that leads to a reduction in the weight of the entire turbine system.